Crafting veteran to baccalaureate nursing programs. - Sikes, Deborah L.; Jones, Melinda Mitchell; Armstrong, Myrna L. (Journal of Professional Nursing, 2026)
Upon leaving the military, veteran health care personnel have difficulty finding commensurate civilian employment, yet their military transcripts document a strong record of health care education and experience. Vigorous Veterans' Bachelor of Science in Nursing (VBSN) programs can provide military personnel with opportunities to become registered nurses. This article describes the incremental planning, curriculum design, prior-learning evaluation option implementation, and student veteran results from one VBSN program with a ten-year history of successful, sustainable delivery. Formation of a multidisciplinary team that possesses ingenuity, knowledge of military culture, and persistence are important for program development. Over 170 veterans have already graduated from this Texas university, with their National Council Licensure Examination (NCLEX) first time pass rates results at 90%, with retakes of 99%. Gender, racial, and ethnic diversity of these graduates exceeds national averages. Information about this VBSN program provides further evidence of effective strategies used to promote development of new veteran-specific programs regarding recruitment, retention, and graduation. • Nursing programs for veterans can provide pathways to become registered nurses. • A multidisciplinary team is needed to support a strong, sustainable VBSN program. • Educating veterans takes ingenuity, knowledge of military culture, and persistence. • A current nursing program of study provides a platform to build a veterans track.